Reef benthic composition and coral communities at the Wuzhizhou Island in the south China sea: The impacts of anthropogenic disturbance. (30th September 2020) - Huang, Jianzhong; Wang, Fengxia; Zhao, Hongwei; Xu, Huili; Liu, Sheng; Xu, Qiang; Wang, Aimin; Li, Xiubao
Abstract: The responses of reef benthic substrata and coral communities to anthropogenic disturbances at the Wuzhizhou Island (WZZ, off the southeast coast of the Hainan Island in the South China Sea) were examined in 2007–2017. A total of 90 scleractinia coral species were recorded at WZZ in 2017. Cluster analysis and ANOSIM analysis of reef benthic composition suggested that WZZ can be divided into the north and south zones with significantly different characteristics. Indeed, anthropogenic disturbance ( i.e., tourism activity and land use) has been intense in the north zone, whereas the south zone has not been as much disturbed. Coral reefs in the north zone suffered from stronger turbidity and nutrient enrichment. Compared with the south zone, the north zone had significantly lower coverage of stony coral (e.g. Acropora, Montipora and Pocillopora ) and soft coral, juvenile coral density but significantly higher coverage of rock/rubble, sand, hydrocoral and sponge. Redundancy analysis demonstrated that turbidity and dissolved nutrients (dissolved inorganic nitrogen or NH4 + ) were the significant factors in explaining the spatial distribution of reef benthic substrata and coral communities in 2017. The remarked decline of live coral cover in the north zone of WZZ during 2007–2016 can be associated with intensive construction, land use change, and tourism development. These results suggested that anthropogenic disturbances may have degenerated environmental conditions and affected the coral reefs at WZZ. Highlights: Scleractinia coral species in 40 genera from 13 families were recorded. Wuzizhou Island can be divided into the north and south zones. Compared with the south zone, the north zone had significantly lower live corals. Reef benthic and coral composition differed between the two zones. Anthropogenic disturbance may take responsibility for the changes of corals.